MANAJEMEN KEPALA SEKOLAH UNTUK MENINGKATKAN KINERJA GURU DAN PRESTASI BELAJAR PESERTA DIDIK DI SMP NEGERI KABUPATEN MAJALENGKA - Muhajir, Muhajir (PT. Solusi Komunikasi Terapan, 2023)
The tittle of thesis is “Principal management to improve teacher’s performance and student’s achievement in junior high school (SMP), Majalengka district (descriptive study in SMP Negeri Majalengka ).” The aim of this research is to find out how far the management of the principal is improving teacher’s performance and student’s achievement in SMP Negeri Majalengka”. Implementation of this school management includes: input, process, and output. The subjects in the research were the principals, teachers, students, and the school commitees. This research use descriptive qualitative approach. Data collection methods in this research are interview, observation , and documentation. After that proceed with data reduction, data presentation, conclusion/verification. The result of analysis and processing of data can be found that there are several problems with the implementation of headmaster management in SMP Negeri kabupaten Majalengka, they are (1) the students have low spirit in learning, (2) Human resources lack understanding of the education system, (3) Another resources such as device, incomplete equipment, and ineaduquate, (4) the sources of funds owned is very limited, and (5) The acquisition of a number of new students who register and are accepted at school is a decrease. Problem solving efforts related to resources , they are (1) Given the guidance to the students and an intensive approach to parents to their children become more active in learning in and out of school, (2) Ask the teacher to allowed the scientific forums, (3) Maximize the function and role of resources by using them as best as possible, (4)Submitba fuding proposal to the goverment or submit this issue to the school commitee to get a solution related to school funding, and (5) Conduct in depth studies on the decline in the number of new students who register and are accepted into the school. The implementation of the management of principals in SMP Negeri kabupaten majalengka, they are (1) the formation of a school committee , (2) Institutionally the management of the principal has not been able to increase the trust and interest of the community, thus impacting the decline in the number of new students, and (3) Be able to improve the security of the school environment. The result of this research need to be reviewed and discussed in more depth, in order to produce the best discovery.